2015
DOI: 10.1021/acs.jmedchem.5b00536
|View full text |Cite
|
Sign up to set email alerts
|

Novel Resveratrol-Based Aspirin Prodrugs: Synthesis, Metabolism, and Anticancer Activity

Abstract: Regular aspirin use has been convincingly shown to reduce the risk of colorectal cancer. However, long-term use of aspirin leads to gastrotoxicity. Herein, we designed and synthesized a novel class of resveratrol-based aspirin prodrugs to simultaneously release aspirin and resveratrol to attenuate the side effects caused by aspirin. Prodrug RAH exerted enhanced anticancer activities which are better than a physical mixture of aspirin and resveratrol as well as each individually. Metabolism of RAH in mice showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…This observation could be due to the structural skeleton composed of 6G and ASA with higher anticancer properties than those of individuals, or 6G + ASA, similar to our previous findings on the combination of resveratrol and ASA25. AMS and MS failed to strengthen the anticancer activity of aspirin, suggesting that methyl ester makes little contribution to aspirin while gingerol ester is a specific building block of GAS for various beneficial physiological effects of aspirin.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This observation could be due to the structural skeleton composed of 6G and ASA with higher anticancer properties than those of individuals, or 6G + ASA, similar to our previous findings on the combination of resveratrol and ASA25. AMS and MS failed to strengthen the anticancer activity of aspirin, suggesting that methyl ester makes little contribution to aspirin while gingerol ester is a specific building block of GAS for various beneficial physiological effects of aspirin.…”
Section: Discussionsupporting
confidence: 87%
“…5i′-p′). Meantime, we found SUA, another metabolite of ASA25, in the feces and urine samples (Fig. 5o′-p′).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Epidemiological studies suggested that the regular intake of aspirin was associated with a reduction in the incidence of malignancies, including colorectal, gastrointestinal, and lung cancer1718. Recent studies demonstrated that aspirin and its metabolite salicylic acid (SA), and their derivatives could induce apoptosis in several colorectal carcinoma cell lines19202122.…”
mentioning
confidence: 99%